2010
DOI: 10.1002/bdd.698
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and biopharmaceutical evaluation of a transdermal patch containing letrozole

Abstract: The purpose of this study was to formulate a drug-in-adhesive (DIA) transdermal patch containing letrozole, a third generation aromatase inhibitor for the treatment of breast cancer, using pressure-sensitive-adhesives (PSAs) and to evaluate the percutaneous penetration and pharmacokinetics of letrozole after transdermal administration, compared with that for the oral route. The formulation factors for such a patch, including the PSAs, enhancers and amount of drug loaded were investigated. Among the tested prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…To completely evaporate any water, the dishes were placed in a hot air oven at 40°C. The backing membrane was used to cover the films and cut into specific dimensions of 202 ± 24 mm with uniform thickness and stored in a desiccator 45. The same amount of SQR was used to prepare pure SQR-loaded transdermal films using the same protocol described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…To completely evaporate any water, the dishes were placed in a hot air oven at 40°C. The backing membrane was used to cover the films and cut into specific dimensions of 202 ± 24 mm with uniform thickness and stored in a desiccator 45. The same amount of SQR was used to prepare pure SQR-loaded transdermal films using the same protocol described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the low systemic levels of letrozole from the patch could decrease the incidence of the aforementioned adverse effects [ 54 ]. Li et al [ 55 ] optimized the delivery from the transdermal patch of letrozole by using various adhesives, permeation enhancers, and different letrozole concentrations. The permeation of letrozole through excised rat skin was significantly higher through the patch with adhesive DURO-TAK ® 87-4098, which lacks a carboxyl group, compared to DURO-TAK ® 87-2677 and 87-2852, the adhesives with a carboxyl group.…”
Section: Transdermal Chemotherapeutics For Breast Cancermentioning
confidence: 99%
“…The permeation of letrozole through excised rat skin was significantly higher through the patch with adhesive DURO-TAK ® 87-4098, which lacks a carboxyl group, compared to DURO-TAK ® 87-2677 and 87-2852, the adhesives with a carboxyl group. It was speculated that the triazole group of letrozole could interact with the carboxyl group to form hydrogen bonds [ 55 ], which could impede the release of the drug from the adhesive with carboxylic groups. Conventional chemical enhancers were used to optimize the permeation, and the results indicated that a combination of azone (10%) with propylene glycol (5%), containing 1.5% of letrozole, was optimal for the adhesive patch [ 55 ].…”
Section: Transdermal Chemotherapeutics For Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, transdermal drug delivery system (TDDS) designs have moved from the conventional reservoir design to the drug-in-adhesive (DIA) matrix design. This DIA design has several advantages including a lightweight and thin presentation providing patients with a more flexible patch while also eliminating the potential for drug leakage (6)(7)(8). The DIA's relatively simple design appearance belies the relatively complex and critical role of the pressuresensitive adhesive (PSA) that must maintain proper adhesive and cohesive properties while concurrently acting as a carrier for the drug substance (9,10).…”
Section: Introductionmentioning
confidence: 99%